Features of vascular regulation of students - future specialists in physical education and sports of different sports specializations with different body lengths - M. Cretu; I.V. Borysenko; V.V. Ushmarova; V.M. Grynyova; V.V. Masych (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
Purpose: to reveal the features of the indicators of the orthostatic test in students with different body lengths and different sport´s specializations, studying in the specialty "Physical education and sports". Material and methods. The study involved 42 students who play sports at the amateur level. The following research methods were used in the work: method of analysis of literary sources; method of determining body length; orthostatic test method; method of determining stroke volume and minute blood volume. Results. The influence of both factors (body length and sport) on the orthostatic test was significant for the following data: systolic blood pressure in the vertical position, diastolic blood pressure in the vertical position; change in diastolic blood pressure when changing body position from horizontal to vertical; Heart rate in vertical and horizontal positions; change in heart rate during the transition from horizontal to vertical position; stroke volume of blood in the vertical position; change in the stroke volume of blood during the transition from horizontal to vertical position; all indicators of minute volume of a blood-groove (p <0,005; p <0,01; p <0,001). The more significant influence of judo and football classes in comparison with running short and medium distances on the indicators of vegetative-vascular regulation was determined: the best indicators - in judo, the next place - in football, then - athletes. It was found that students with a body length of more than 190 cm have difficulty with vegetative-vascular regulation. Conclusions. To improve the adaptive capacity of vascular regulation to change the position of the body from horizontal to vertical in tall athletes is effective to use any exercise, but the most effective exercises that activate aerobic and anaerobic glycolytic energy systems. Also useful are exercises that require frequent transitions from lying down (sitting) to standing position, as well as changes in the direction of movement.